Detection of Intrusions and Malware, and Vulnerability Assessment 8th International Conference; DIMVA 2011, Amsterdam, The Netherlands, July 7-8, 2011. Proceedings - Holz, Thorsten; Bos, Herbert (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 8th International Conference on Detection of Intrusions and Malware, and Vulnerability Assessment, DIMVA 2011, held in Amsterdam, the Netherlands, in July 2011. The 11 full papers presented together with two short papers were carefully reviewed and selected from 41intial  submissions. The papers are organized in topical sections on network security, attacks, Web security, and host security.